The Domain Structure of ICAM-1 and the Kinetics of Binding to Rhinovirus - Casasnovas, José M. (American Society for Microbiology, 1998)
Fragments of intercellular adhesion molecule 1 (ICAM- 1) containing only the two most N terminal of its five immunoglobulin SF domains bind to rhinovirus 3 with the same affinity and kinetics as a fragment with the entire extracellular domain. The fully active two-domain fragments contain 5 or 14 more residues than a previously described fragment that is only partially active. Comparison of X-ray crystal structures show differences at the bottom of domain 2. Four different glycoforms of ICAM- 1 bind with identical kinetics.